RESPON PEMBERIAN PUPUK AB-MIX DAN BERBAGAI PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN TANAMAN TERUNG UNGU (Solanum melongena L.) SECARA HIDROPONIK DENGAN SISTEM WICK - Deddy Wahyudin Purba; Jian Maulana (Universitas Muhammadiyah Mataram, 2021)
This study aimed to determine the effect of AB Mix fertilizer and various liquid organic fertilizers on the growth of purple eggplant (Solanum melongena L.) hydroponically with an axis system. The design used was a Randomized Block Design (RAK). While the treatment design is factorial consisted of two factors studied, namely: 1. AB Mix (A) fertilizer consists of 3 levels A1: 500 ppm/plot, A2: 100 ppm/plot, A3: 1500/plot. 2. Various liquid organic fertilizers (C) with a dose of 40 cc/plot: C1 (POC Peel), C2 (POC HANTU), and C3 (POC Banana Weevil), with three times replications. Parameters observed were plant height (cm), stem diameter (mm), number of leaves (strands), flowering time (days), and number of flowers (days). The results showed that Mixed AB fertilizer has no significant effect on plant height and stem diameter, but significantly affects the number of leaves, flowering time, and the flowers' number. The application of various organic fertilizers did not show a significant effect in almost all parameters except for the flowering time and obtained the best organic fertilizer yield, namely POC Bonggol Pisang (C3). In addition, the interaction of AB Mix fertilizer and various organic fertilizers did not significantly affect all the parameters observed.